2014
DOI: 10.1093/ajh/hpt290
|View full text |Cite
|
Sign up to set email alerts
|

Association of Morning and Evening Blood Pressure at Home With Asymptomatic Organ Damage in the J-HOP Study

Abstract: Morning BP and evening BP provide equally useful information for subclinical target organ damage, yet multivariate modeling highlighted the stand-alone predictive ability of morning BP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 37 publications
1
58
3
Order By: Relevance
“…2,12,13 Second, morning BP is more reflective of certain pathophysiological conditions compared with evening BP, such as obesity, sleep apnea, and various target-organ damages (eg, left ventricular hypertrophy, albuminuria, and vascular dysfunction). 19,25,26 However, in our study, the association of morning SBP with stroke risk was independent of organ damage markers (ie, microalbuminuria and brain natriuretic peptide values). This suggests that higher morning SBP may not be merely an epiphenomenon of comorbidities, but causally related to stroke occurrence.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…2,12,13 Second, morning BP is more reflective of certain pathophysiological conditions compared with evening BP, such as obesity, sleep apnea, and various target-organ damages (eg, left ventricular hypertrophy, albuminuria, and vascular dysfunction). 19,25,26 However, in our study, the association of morning SBP with stroke risk was independent of organ damage markers (ie, microalbuminuria and brain natriuretic peptide values). This suggests that higher morning SBP may not be merely an epiphenomenon of comorbidities, but causally related to stroke occurrence.…”
Section: Discussioncontrasting
confidence: 72%
“…The Japan Morning Surge-Home Blood Pressure (J-HOP) study 19 is a prospective observational study (University Hospital Medical Information Network Clinical Trials Registry, UMIN000000894) of 4310 patients with a history of or risk factors for CVD, or both, who were recruited between 2005 and 2012 and followed up through March 2015 by 75 doctors at 71 institutions (45 primary practices, 22 hospital-based outpatient clinics, and 4 specialized university hospitals; see online-only Data Supplement). Details of the study design and methods are described in the online-only Data Supplement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that weekly averaged BP could be a good prognostic marker of the incidence of both cardiovascular events and all-cause mortality in hemodialysis patients [25]. It has been reported that home-measured BP, especially systolic BP in the morning on hemodialysis days, can provide pivotal information for the management of hemodialysis patients [26,27]. Thus, home-measured BP was evaluated for a week before and after switching.…”
Section: Discussionmentioning
confidence: 99%
“…We previously performed a cross-sectional study to explore the target home BP level in T2DM patients as a sub-analysis of the Japan Morning Surge Home Blood Pressure (J-HOP) Study (28). The J-HOP study is a prospective observational study evaluating the predictive values of home BP for cardiovascular events in Japanese subjects with any cardiovascular risk factors (29). The study enrolled 4,310 patients (mean age 64.9± 10.9 years; 47.0% men), and clinic and home BP monitoring were performed.…”
Section: New Proposed Target Home Bp In Subjects With T2dmmentioning
confidence: 99%